Spontaneous homeotic mutants and genetic control of floral organ identity in a ranunculid. Issue 3 (12th November 2020) - Martínez‐Gómez, Jesús; Galimba, Kelsey D.; Coté, Erin Y.; Sullivan, Alessandra M.; Di Stilio, Verónica S.
Abstract: The regulation of floral organ identity was investigated using a forward genetic approach in five floral homeotic mutants of Thalictrum, a noncore eudicot. We hypothesized that these mutants carry defects in the floral patterning genes. Mutant characterization comprised comparative floral morphology and organ identity gene expression at early and late developmental stages, followed by sequence analysis of coding and intronic regions to identify transcription factor binding sites and protein–protein interaction (PPI) motifs. Mutants exhibited altered expression of floral MADS‐box genes, which further informed the function of paralogs arising from gene duplications not found in reference model systems. The ensuing modified BCE models for the mutants supported instances of neofunctionalization (e.g., B‐class genes expressed ectopically in sepals), partial redundancy (E‐class), or subfunctionalization (C‐class) of paralogs. A lack of deleterious mutations in the coding regions of candidate floral MADS‐box genes suggested that cis ‐regulatory or trans ‐acting mutations are at play. Consistent with this hypothesis, double‐flower mutants had transposon insertions or showed signs of transposon activity in the regulatory intron of AGAMOUS ( AG ) orthologs. Single amino acid substitutions were also found, yet they did not fall on any of the identified DNA binding or PPI motifs. In conclusion, we present evidence suggesting that transposon activity and regulatory mutations in floral homeotic genes likely underlie the striking phenotypes of these Thalictrum floral homeotic mutants. Abstract : In this study, we characterize spontaneous homeotic Thalictrum flower mutants to test the hypothesis that changes in floral MADS‐box genes are responsible for their distinct morphologies. We find altered B‐, C‐, and E‐class expression, highlighting the differential role of these frequently duplicated genes in floral organ identity and elaboration in a noncore eudicot. Research Highlights: Flower homeotic mutants of Thalictrum showed developmental defects consistent with altered expression of floral organ identity genes. Modified BCE models illustrated the divergence of paralogs. Transposon activity and regulatory mutations are likely causes.